Positive electrode material, preparation method thereof and battery
By covering the surface of spinel nickel lithium manganate positive electrode material with a cladding layer of materials such as phosphate and LiFePO4, the problem of poor compatibility of this material with the existing power battery system is solved, and the cycling performance and high-temperature storage stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411860703.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
AI Technical Summary
The spinel type nickel lithium manganate positive electrode material has poor compatibility with the existing power battery system, resulting in poor interface stability, manganese ion dissolution and SEI film destruction, affecting the battery cycle stability.
The surface of spinel nickel lithium manganate is coated with a coating layer containing materials such as monohydrogen phosphate ions and/or dihydrogen phosphate ions and LiFePO4. LiMnPO4 is generated by reacting with dissolved Mn2+ to avoid the migration of Mn2+ to the negative electrode, and combine with H+ in the electrolyte to delay the dissolution of the transition metal.
It effectively improves the interface stability of the positive electrode material, reduces Mn2+ dissolution and SEI film damage, and enhances the cycling performance of the battery and high-temperature storage stability.
Smart Images

Figure CN119812246A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material and a preparation method thereof, and a battery. Background Art
[0002] Spinel-type lithium nickel manganese oxide cathode materials are often used in high-energy-density power battery systems because of their advantages such as high voltage platform, high energy density, low cost and high safety performance. However, due to their high reaction potential (>4.6V), they have poor compatibility with existing power battery systems, especially strong oxidation of electrolytes. The interface stability between the cathode and the electrolyte is poor, and there are a large number of positive electrode interface side reactions, which cause manganese ions to dissolve into the electrolyte and destroy the SEI film on the surface of the negative electrode. The reorganization of the SEI film further consumes the electrolyte, affecting the cycle stability of the battery system. Summary of the invention
[0003] Based on this, the present application provides a positive electrode material and a preparation method thereof, and a battery to solve the above technical problems.
[0004] The first aspect of the present application provides a positive electrode material, which includes a core and a coating layer coating the core, wherein:
[0005] The core is lithium nickel manganese oxide with a spinel structure;
[0006] The coating layer includes a first coating agent and a second coating agent, the first coating agent includes monohydrogen phosphate ions and / or dihydrogen phosphate ions, and the second coating agent includes LiFePO 4 、FePO 4 、NiPO 4 、LiCoPO 4 , AlF 3 、AlCl 3 and Al(NO 3 ) 3 One or more of .
[0007] In some embodiments, the particle size D50 of the first coating agent is ≥ 0.4 μm.
[0008] In some embodiments, the particle size D50 of the second coating agent is ≥ 0.6 μm;
[0009] And / or the primary particle size of the second coating agent is 100 nm~300 nm.
[0010] In some embodiments, the mass ratio of the coating layer to the core is (1:99) to (3:97).
[0011] In some embodiments, the mass ratio of the first coating agent to the second coating agent is 1:(1-3).
[0012] In some embodiments, the coating layer has a thickness of 15 nm to 250 nm.
[0013] In some embodiments, the first coating agent includes Zr(HPO 4 ) 2 、Ti(HPO 4 ) 2 、W(HPO 4 ) 2 、NaH 2 PO 4 、Na 2 HPO 4 and LiH 2 PO 4 One or more of .
[0014] The second aspect of the present application provides a method for preparing the positive electrode material provided in the first aspect, comprising the following steps:
[0015] The weighed spinel-structured lithium nickel manganese oxide and the coating layer material are mixed evenly to prepare a mixture;
[0016] The mixed material is kept at a preset temperature for a preset time, cooled to room temperature at a preset cooling rate, and sieved to obtain a positive electrode material.
[0017] In some embodiments, the preset temperature is 500°C to 700°C.
[0018] In some embodiments, the preset time is 4h~6h.
[0019] In some embodiments, the preset cooling rate is 2°C / min to 6°C / min.
[0020] The third aspect of the present application provides a battery, including a positive electrode sheet and a negative electrode sheet, the positive electrode sheet includes a current collector and a positive electrode active layer arranged on the current collector, and the positive electrode active layer includes the positive electrode material provided in the first aspect above.
[0021] In the present application, a coating layer comprising a first coating agent and a second coating agent is coated on the surface of spinel lithium nickel manganese oxide, wherein the first coating agent comprises dihydrogen phosphate ions (H 2 PO 4 - ) and / or monohydrogen phosphate ions (HPO 4 2- ), which can react with dissolved Mn 2+ LiMnPO is generated by the reaction 4 , avoiding Mn 2+ Migrate to the negative electrode during the charge and discharge process, destroy the SEI film on the negative electrode surface; at the same time, it can react with H in the electrolyte. +The second coating agent has a stable surface phase structure and is coated on the surface of the spinel nickel manganese oxide core, isolating the spinel nickel manganese oxide core from the electrolyte, delaying the side reaction of the surface nickel manganese oxide core material under high potential, and reducing the generation of HF byproduct. 2+ The dissolution migrates to the negative electrode during the charge and discharge process, destroying the SEI film on the negative electrode surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Flow chart of a method for preparing a positive electrode material in one embodiment of the present application. DETAILED DESCRIPTION
[0023] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0024] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0026] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0027] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100~150 nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).
[0028] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0030] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, mentioning that the method may also include step (c) means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0032] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0033] The first aspect of the present application provides a positive electrode material, which includes a core and a coating layer coating the core, wherein:
[0034] The core is lithium nickel manganese oxide with a spinel structure;
[0035] The coating layer includes a first coating agent and a second coating agent, the first coating agent includes monohydrogen phosphate ions and / or dihydrogen phosphate ions, and the second coating agent includes LiFePO 4 、FePO 4 、NiPO 4 、LiCoPO 4 , AlF 3 、AlCl 3 and Al(NO 3 ) 3 One or more of .
[0036] In some embodiments, the particle size D50 of the first coating agent is ≥ 0.4 μm, including but not limited to 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, and 0.8 μm.
[0037] In some embodiments, the particle size D50 of the second coating agent is ≥ 0.6 μm, including but not limited to 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1 μm.
[0038] In some embodiments, the primary particle size of the second coating agent is 100 nm to 300 nm, including but not limited to 100 nm, 150 nm, 200 nm, 250 nm, and 300 nm.
[0039] In some embodiments, the mass ratio of the coating layer to the core is (1:99) to (3:97).
[0040] In some embodiments, the mass ratio of the first coating agent to the second coating agent is 1:(1-3), including but not limited to 1:1, 1:1.5, 1:2, 1:2.5, 1:3.
[0041] In some embodiments, the thickness of the coating layer is 15 nm to 250 nm, including but not limited to 15 nm, 30 nm, 50 nm, 75 nm, 100 nm, 125 nm, 175 nm, 200 nm, and 250 nm.
[0042] In some embodiments, the first coating agent includes Zr(HPO 4 ) 2 、Ti(HPO 4 ) 2 、W(HPO 4 ) 2 、NaH 2 PO 4 、Na 2 HPO 4 and LiH 2 PO 4 One or more of .
[0043] like Figure 1 As shown, the second aspect of the present application provides a method for preparing the positive electrode material provided in the first aspect, comprising the following steps:
[0044] S1. Evenly mix the weighed spinel lithium nickel manganese oxide and the coating layer material to prepare a mixture;
[0045] S2. After the mixture is kept at a preset temperature for a preset time, it is cooled to room temperature at a preset cooling rate, and sieved to obtain a positive electrode material.
[0046] In some embodiments, the preset temperature is 500° C. to 700° C., including but not limited to 500° C., 550° C., 600° C., 650° C., and 700° C. Further, the preset temperature is 600° C.
[0047] In some embodiments, the preset time is 4 hours to 6 hours, including but not limited to 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours. Further, the preset time is 5 hours.
[0048] In some embodiments, the preset cooling rate is 2°C / min to 6°C / min, including but not limited to 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, and 6°C / min. Further, the preset cooling rate is 5°C / min.
[0049] In some embodiments, the step S1 further includes the following steps:
[0050] Weigh the appropriate proportion of Ni 0.25 Mn 0.75 (OH) 2 Precursor and Li 2 CO 3 , mixing the two uniformly to obtain a mixture;
[0051] The mixture is placed in a box-type atmosphere furnace, heated to a certain temperature in an air atmosphere, kept warm, cooled to room temperature, ground, and sieved to obtain a spinel-type lithium nickel manganese oxide material. For the convenience of description, the spinel-structured lithium nickel manganese oxide material is abbreviated as LNMO.
[0052] In the present application, a coating layer comprising a first coating agent and a second coating agent is coated on the surface of spinel nickel manganese oxide, wherein the first coating agent comprises monohydrogen phosphate ions and / or dihydrogen phosphate ions, which can react with dissolved Mn 2+ LiMnPO is generated by the reaction 4 , avoiding Mn 2+ Migrate to the negative electrode during the charge and discharge process, destroy the SEI film on the negative electrode surface; at the same time, it can react with H in the electrolyte. + The second coating agent has a stable surface phase structure and is coated on the surface of the spinel nickel manganese oxide core, isolating the spinel nickel manganese oxide core from the electrolyte, delaying the side reaction of the surface nickel manganese oxide core material under high potential, and reducing the generation of HF byproduct. 2+ The dissolution migrates to the negative electrode during the charge and discharge process, destroying the SEI film on the negative electrode surface.
[0053] The third aspect of the present application provides a battery, including a positive electrode sheet and a negative electrode sheet, the positive electrode sheet includes a positive electrode collector and a positive electrode active layer arranged on the current collector, and the positive electrode active layer includes the positive electrode material provided in the first aspect above.
[0054] In some embodiments, the positive electrode sheet includes a positive electrode collector. Exemplarily, the positive electrode collector may be aluminum (Al), but is not limited thereto.
[0055] In some embodiments, the positive electrode active layer further includes a positive electrode conductive agent and a positive electrode binder. The positive electrode conductive agent can make the positive electrode sheet have a certain conductivity. The positive electrode binder can improve the bonding between the positive electrode material particles and also improve the bonding between the positive electrode material layer and the positive electrode current collector.
[0056] In some embodiments, the positive electrode conductor may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials. For example, at least one of carbon black, graphite, acetylene black (e.g., KETCHEN™ black or DENKA™ black), carbon nanofibers, single-walled carbon nanotubes, multi-walled carbon nanotubes, and conductive polymer fibers.
[0057] In some embodiments, non-limiting examples of the positive electrode binder include polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate (SA), and at least one of lithium alginate.
[0058] In some embodiments, the negative electrode sheet includes a negative electrode current collector, a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder. The negative electrode conductive agent can make the negative electrode sheet have a certain conductivity. The negative electrode binder can improve the bonding between the negative electrode active material particles and also improve the bonding between the negative electrode material layer and the negative electrode current collector.
[0059] In some embodiments, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12, Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0060] In some embodiments, the negative electrode conductive agent includes at least one of carbon black, graphite, acetylene black (eg, KETCHEN™ black or DENKA™ black), carbon nanofibers, single-walled carbon nanotubes, multi-walled carbon nanotubes, and conductive polymer fibers.
[0061] In some embodiments, the negative electrode binder includes at least one of polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), polyacrylic acid (PAA), sodium alginate (SA), and lithium alginate.
[0062] In some embodiments, the battery further comprises a diaphragm. The diaphragm is disposed between the positive electrode sheet and the negative electrode sheet to achieve long-term effective isolation between the positive and negative electrodes. Any diaphragm in the prior art can be used in the present application. The diaphragm can be a common diaphragm or a functional diaphragm, such as a flame retardant diaphragm with flame retardant material added.
[0063] In some embodiments, the battery further includes an electrolyte.
[0064] It is understandable that in the present application, there is no particular limitation on the types of positive electrode current collector, negative electrode current collector and electrolyte. Any known types of positive electrode current collector, negative electrode current collector and electrolyte can be used as long as it complies with the overall inventive concept of the present application.
[0065] The embodiments of the present application will be described in more detail below through specific examples. However, the embodiments of the present application are not limited to these examples.
[0066] The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0067] Example 1
[0068] Preparation of positive electrode materials:
[0069] Weigh 179.8 g of Ni 0.25 Mn 0.75 (OH) 2 Precursor and 36.9 g of Li 2 CO 3 , add the two into a mixer and mix evenly to obtain a mixture.
[0070] The mixture was loaded into a sagger with a certain thickness and transferred to a box-type atmosphere furnace. The temperature was increased to 900°C at a heating rate of 3°C / min in a sufficient air atmosphere, kept at this temperature for 12 hours, and then cooled at a cooling rate of 5°C / min. After ultracentrifugal grinding and sieving, LNMO was obtained.
[0071] Weigh 0.8g of the first coating agent Na 2 HPO 4 Powder (D50 is 0.4 μm), 1.6 g of the second coating agent small-particle LiFePO 4 The powder (D50 is 0.6 μm, the first particle size is 80 nm) and 57.6 g of LNMO are added into the same high-speed mixer and mixed evenly to prepare a mixture.
[0072] The mixed material was transferred to a box-type atmosphere furnace and kept at 600°C for 5 hours in a sufficient air atmosphere, then cooled to room temperature at a rate of 5°C / min, and obtained after screening to obtain a positive electrode material. The coating layer formed by the first coating agent and the second coating agent had a thickness of 50 nm.
[0073] Positive electrode preparation:
[0074] The positive electrode material, binder PVDF, conductive carbon black, and CNT conductive agent are mixed in a mass ratio of 92:4:3:1, and wet homogenized in an oily system to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, and die cutting processes.
[0075] Preparation of negative electrode:
[0076] Graphite, conductive carbon black, CMC and SBR were mixed in a ratio of 96:2:1:1, and wet homogenized with water as solvent to obtain slurry. The slurry was coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, slitting and die cutting.
[0077] Preparation of the battery:
[0078] After the positive electrode sheet, separator, and negative electrode sheet are stacked, the tabs are welded, and packaged and then thoroughly dried, a battery cell is obtained. 1 mol / L LiPF 6The electrolyte (the volume ratio of EC / EMC / DEC is 3:5:2) is vacuum packaged, hot pressed, aged, degassed, and sealed. After the battery cell is clamped for capacity division and OCV measurement, it can be used for various performance tests. The rated capacity of the battery is 6Ah.
[0079] Example 2
[0080] Preparation of positive electrode materials:
[0081] Weigh 179.8 g of Ni 0.25 Mn 0.75 (OH) 2 Precursor and 36.9 g of Li 2 CO 3 , add the two into a mixer and mix evenly to obtain a mixture.
[0082] The mixture was loaded into a sagger with a certain thickness and transferred to a box-type atmosphere furnace. The temperature was increased to 900°C at a heating rate of 3°C / min in a sufficient air atmosphere, kept at this temperature for 12 hours, and then cooled at a cooling rate of 5°C / min. After ultracentrifugal grinding and sieving, LNMO was obtained.
[0083] Weigh 1g of the first coating agent nanoscale γ-phase Zr(HPO 4 ) 2 Powder (D50 is 0.6μm), 1g of the second coating agent small-particle LiFePO 4 powder (D50 is 0.6 μm, the first particle size is 200 nm) and 98 g of LNMO are added into the same high-speed mixer and mixed evenly to prepare a mixture.
[0084] The mixture was transferred to a box-type atmosphere furnace and kept at 600°C for 5 hours in a sufficient air atmosphere, then cooled to room temperature at a rate of 5°C / min, and the positive electrode material was obtained after sieving. The coating layer formed by the first coating agent and the second coating agent had a thickness of 100 nm.
[0085] Positive electrode preparation:
[0086] The positive electrode material, binder PVDF, conductive carbon black, and CNT conductive agent are mixed in a mass ratio of 92:4:3:1, and wet homogenized in an oily system to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, and die cutting processes.
[0087] Preparation of negative electrode:
[0088] Graphite, conductive carbon black, CMC and SBR were mixed in a ratio of 96:2:1:1, and wet homogenized with water as solvent to obtain slurry. The slurry was coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, slitting and die cutting.
[0089] Preparation of the battery:
[0090] After the positive electrode sheet, separator, and negative electrode sheet are stacked, the tabs are welded, and packaged and then thoroughly dried, a battery cell is obtained. 1 mol / L LiPF 6 The electrolyte (the volume ratio of EC / EMC / DEC is 3:5:2) is vacuum packaged, hot pressed, aged, degassed, and sealed. After the battery cell is clamped for capacity division and OCV measurement, it can be used for various performance tests. The rated capacity of the battery is 6Ah.
[0091] Example 3
[0092] The difference between this embodiment and implementation 2 is that: Zr(HPO 4 ) 2 The D50 of powder is different, LiFePO 4 The first particle sizes of the powders are different.
[0093] Example 4
[0094] The difference between this embodiment and implementation 2 is that: Zr(HPO 4 ) 2 The D50 of powder is different, LiFePO 4 The first particle sizes of the powders are different.
[0095] Example 5
[0096] The difference between this embodiment and embodiment 2 is that the mass ratio of the first coating agent to the second coating agent in the coating layer of the positive electrode material is different, and the mass ratio of the coating layer to the core is different.
[0097] Example 6
[0098] The difference between this embodiment and embodiment 2 is that the mass ratio of the first coating agent to the second coating agent in the coating layer of the positive electrode material is different, and the mass ratio of the coating layer to the core is different.
[0099] Example 7
[0100] The difference between this embodiment and embodiment 2 is that the first coating agent and the second coating agent in the coating layer of the positive electrode material are made of different materials, and the D50 of the second coating agent is different.
[0101] Example 8
[0102] The difference between this embodiment and embodiment 2 is that the first coating agent and the second coating agent in the coating layer of the positive electrode material are made of different materials, the D50 of the second coating agent is different, and the coating layer thickness is different.
[0103] Example 9
[0104] The difference between this embodiment and embodiment 2 is that the first coating agent and the second coating agent in the coating layer of the positive electrode material are made of different materials and the coating layer thicknesses are different.
[0105] Example 10
[0106] The difference between this embodiment and embodiment 2 is that the first coating agent and the second coating agent in the coating layer of the positive electrode material are made of different materials and the coating layer thicknesses are different.
[0107] Embodiment 11
[0108] The difference between this embodiment and embodiment 2 is that the D50 of the first coating agent in the coating layer of the positive electrode material is different.
[0109] Example 12
[0110] The difference between this embodiment and embodiment 2 is that the D50 of the second coating agent in the coating layer of the positive electrode material is different.
[0111] Example 13
[0112] The difference between this embodiment and embodiment 2 is that the mass ratio of the first coating agent and the second coating agent in the coating layer of the positive electrode material is different.
[0113] Comparative Example 1
[0114] The difference between this comparative example and Example 2 is that no coating layer is provided on the inner core surface of the positive electrode material.
[0115] Comparative Example 2
[0116] The difference between this comparative example and Example 2 is that the coating layer on the surface of the positive electrode material only includes the second coating agent.
[0117] Comparative Example 3
[0118] The difference between this comparative example and Example 2 is that the coating layer on the surface of the positive electrode material only includes the first coating agent.
[0119] The test parameters of the embodiments and comparative examples are summarized in Table 1 below:
[0120] Table 1
[0121]
[0122] Test Case
[0123] 25℃ Cycle Test
[0124] The battery cells were transferred to a 25°C constant temperature box for charge and discharge cycle test experiments. The charge and discharge test steps were as follows: (1) 0.33C constant current discharge to 3.5V; (2) 0.33C constant current constant voltage charge to 4.9V (cut-off current 0.05C); (3) 0.33C rate constant current discharge to 3.5V. The 25°C cycle test results are shown in Table 2.
[0125] 45℃ Cycle Test
[0126] The battery cells were transferred to a 45°C constant temperature box for charge and discharge cycle test experiments. The charge and discharge test steps were as follows: (1) 0.33C constant current discharge to 3.5V; (2) 0.33C constant current constant voltage charge to 4.9V (cut-off current 0.05C); (3) 0.33C rate constant current discharge to 3.5V. The 45°C cycle test results are shown in Table 2.
[0127] 55℃ high temperature storage test
[0128] The fully charged soft-pack battery cells were stored in a 60°C constant temperature oven, and the volume of the fresh fully charged battery cells was measured using the drainage method. Every 10 days, the battery cells were taken out of the oven, left to stand at room temperature, and the battery volume was tested. The battery cells were then charged to 4.8V at a rate of 0.33C. The volume change of the battery cells after 30 days was recorded, corresponding to the gas production ratio of the battery cells. The test results are shown in Table 2.
[0129] Transition Metal Dissolution Test
[0130] The soft-packed battery cell with low SOC after cycling was disassembled, and the negative electrode sheet was taken out. After the negative electrode sheet was completely oxidized and turned black in the external environment, it was soaked in DMC for 24 hours and then scraped for powder treatment. The powder material was washed, filtered, dried, and ground, and sent to the inductively coupled plasma atomic emission spectrometer ICP to analyze the relative content of Mn and Ni elements in the sample. The test results are shown in Table 2.
[0131] Table 2
[0132]
[0133] By comparing the test data of the embodiment and the comparative example, it can be seen that the technical solution in the present application enhances the cycle performance of the battery, avoids gas production under high temperature conditions, and at the same time avoids the migration of positive electrode transition metal ions to the negative electrode during the charging and discharging process, thereby destroying the SEI film on the surface of the negative electrode.
[0134] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0135] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A positive electrode material, characterized in that: It comprises a core and a coating layer covering the core, wherein: The core is lithium nickel manganese oxide having a spinel structure; The coating layer includes a first coating agent and a second coating agent, the first coating agent includes monohydrogen phosphate ions and / or dihydrogen phosphate ions, and the second coating agent includes one or more of LiFePO4, FePO4, NiPO4, LiCoPO4, AlF3, AlCl3 and Al(NO3)3.
2. The positive electrode material according to claim 1, characterized in that The particle size D50 of the first coating agent is ≥0.4 μm.
3. The positive electrode material according to claim 1, characterized in that The particle size D50 of the second coating agent is ≥ 0.6 μm; And / or the primary particle size of the second coating agent is 100nm~300nm.
4. The positive electrode material according to claim 1, characterized in that The mass ratio of the coating layer to the core is (1:99) to (3:97).
5. The positive electrode material according to claim 1, characterized in that The mass ratio of the first coating agent to the second coating agent is 1:(1-3).
6. The positive electrode material according to claim 1, characterized in that The thickness of the coating layer is 15 nm to 250 nm.
7. The positive electrode material according to claim 1, characterized in that The first coating agent includes one or more of Zr(HPO4)2, Ti(HPO4)2, W(HPO4)2, NaH2PO4, Na2HPO4 and LiH2PO4.
8. A method for preparing a positive electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The weighed spinel-structured lithium nickel manganese oxide and the coating layer material are mixed evenly to prepare a mixture; The mixed material is kept at a preset temperature for a preset time, cooled to room temperature at a preset cooling rate, and sieved to obtain a positive electrode material.
9. The method for preparing the positive electrode material according to claim 8, characterized in that: The preset temperature is 500°C to 700°C; and / or the preset time is 4h~6h; And / or the preset cooling rate is 2℃ / min~6℃ / min.
10. A battery, characterized in that: The invention comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a current collector and a positive electrode active layer arranged on the current collector, and the positive electrode active layer comprises the positive electrode material according to any one of claims 1 to 7.